AI Dermatology vs. Dermatologist Diagnosis: A Comparative Analysis of Accuracy and the Future of Digital Health - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
AI Dermatology vs. Dermatologist Diagnosis: A Comparative Analysis of Accuracy and the Future of Digital Health The integration of Artificial Intelligen...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care